2016
DOI: 10.5812/ircmj.27893
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Psoriasis Patients from Social Stigma and Rejection: A Qualitative Study

Abstract: BackgroundPsoriasis is a common, chronic skin disease that causes challenges such as stigma and labeling from both the community and individuals due to its effects on appearance.ObjectivesThe objective of this study was to describe and explain the social stigma and rejection experienced by patients with psoriasis.Patients and MethodsThe present research is a qualitative study with a hermeneutic phenomenological approach conducted among psoriasis patients referring to the dermatology clinic and ward of Imam Kho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 29 publications
4
47
0
Order By: Relevance
“…The emotional burden of skin diseases is enormous, and has a negative impact on QoL. [31] Ghorbanibirgani et al found that patients with psoriasis experienced feelings of stigma that led to a weakening of the self-concept, [32] which is consistent with our findings. Ghorbanibirgani et al further revealed that patients with psoriasis were rejected by others, causing them a painful experience and leading to the decision not to disclose their disease.…”
Section: Discussionsupporting
confidence: 92%
“…The emotional burden of skin diseases is enormous, and has a negative impact on QoL. [31] Ghorbanibirgani et al found that patients with psoriasis experienced feelings of stigma that led to a weakening of the self-concept, [32] which is consistent with our findings. Ghorbanibirgani et al further revealed that patients with psoriasis were rejected by others, causing them a painful experience and leading to the decision not to disclose their disease.…”
Section: Discussionsupporting
confidence: 92%
“…This has been proven by measured assessments of the general population (e.g. FORSA surveys), people affected as well as many descriptions by patient organizations …”
Section: Introductionmentioning
confidence: 99%
“…FORSA surveys), 25 people affected as well as many descriptions by patient organizations. [26][27][28] Consensus exists that there is comparatively little evidence on the effectiveness of destigmatization measures in skin diseases. Experiences in anti-stigma efforts of other chronic diseases, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several psychological constructs have been studied in clinical samples of patients with psoriasis, e.g., depression [6], anxiety [7], embitterment [8], stigmatization [9], isolation [10], quality of life [11] and body image [12,13]. All these studies report worse outcomes for patients with psoriasis than for controls, i.e., more depression, more anxiety, more embitterment, more stigmatization, more isolation, less quality of life and worse body image.…”
Section: Introductionmentioning
confidence: 99%